Hereditary hemorrhagic telangiectasia, liver disease and elevated serum testosterone (Osler–Weber–Rendu syndrome): a case report. (December 2017) - Dissanayake, R.; Wickramarathne, K.; Seneviratne, S.; Perera, S.; Fernando, M.; Wickramasinghe, V.
Abstract Background A Sri Lankan girl with hereditary hemorrhagic telangiectasia (Osler–Weber–Rendu syndrome) is described. Case presentation She presented with recurrent spontaneous epistaxis, pulmonary arterio venous malformation and oral telangiectasia. A diagnosis of Hereditary hemorrhagic telangiectasia (Osler–Weber–Rendu syndrome) was made based on the presence of three Curacao criteria (out of four). Evaluations of her jaundice revealed chronic parenchymal liver disease with multiple nodules in the liver with early portal hypertension. She had a muscular build, with elevated serum testosterone but low serum dehydroepiandrosterone sulphate levels. This could be attributed to impaired sulfation of dehydroepiandrosterone due to portocaval shunting of blood, leading to hyperandrogenemia. Conclusions Hyperandorogenemia due impaired sulfation of dehydroepiandrosterone as a result of portocaval shunting is seen in Hereditary haemorrhagic telangiectasia.